2009
DOI: 10.1002/cncr.24245
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophage inhibitory factor in tumorigenesis and central nervous system tumors

Abstract: Poly(trimethoxy silylpropylaniline), a nanoporous (pore diameter of 2.4 nm), electroactive (stable reversible redox characteristics), electrochromic (yellow at −0.10 V, blue green at +0.50 V, and dark green at +0.70 V), and pH‐sensitive, silica–polyaniline (PANI) hybrid material (designated as KGM‐1) has been synthesized in powder form by a simple one‐pot chemical synthesis as well as a “thin nanolayered film” by cyclic voltammetry. High‐resolution transmission image of KGM‐1 informs that the particles are sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 158 publications
(124 reference statements)
3
55
0
Order By: Relevance
“…MIF is a highly conserved multipotential protein that acts variously as a pro-inflammatory cytokine, a pituitary hormone, and as a cell proliferation and migration factor (Bifulco et al, 2008). It is a unique cytokine affecting multiple processes fundamental to tumorigenesis (Bach et al, 2009). In addition, MIF has prognostic value in human colorectal cancer because its expression correlates with aggressiveness of the cancer (Legendre et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIF is a highly conserved multipotential protein that acts variously as a pro-inflammatory cytokine, a pituitary hormone, and as a cell proliferation and migration factor (Bifulco et al, 2008). It is a unique cytokine affecting multiple processes fundamental to tumorigenesis (Bach et al, 2009). In addition, MIF has prognostic value in human colorectal cancer because its expression correlates with aggressiveness of the cancer (Legendre et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For further investigation on these transcripts we chose two highly represented genes, macrophage migration inhibitory factor (MIF) and metallothionein 2A (MT2A). They have recently been associated with tumorigenesis: MIF gene with tumor growth (Bifulco et al, 2008;Bach et al, 2009), and MT2A gene with breast cancer (Jin et al, 2004) and chemoresistance in ovarian cancers (L' Espe´rance et al, 2006). We examined whether the expression of MIF and MT2A is influenced by eIF3m in the HCT-116 cells.…”
Section: Identification Of Eif3m-associated Transcripts By Ribonomicsmentioning
confidence: 99%
“…Despite its discovery in the mid-1960s as a T-cell-derived factor that modulated the motility of monocytes, macrophage migration inhibitory factor (MIF) has been shown to be involved in cancers [9][10][11][12][13]. Interestingly, both circulating and intracellular levels of MIF were elevated in patients with cancers, and the levels of MIF were closely correlated with tumor aggressiveness and metastatic potential, suggesting that MIF contributed to disease severity and survival [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting analysis of HUVEC cells lines showed higher MIF, ERK1, VEGF protein expression than in normal cholangiocytes. As described above, previous studies showed that MIF was overexpressed in multiple tumors, moreover, MIF was associated with blood-supply of cancer [11,12]. In addition, Fujiwaki et al found that expression of VEGF progressively increased in the progress of normal cervical epithelium→carcinoma in situ→invasive carcinoma [13].…”
Section: Discussionmentioning
confidence: 99%